A aprendizagem de uma criança com altas habilidades/superdotação e transtorno de Asperger - Silveira, Sheila Torma da (2014)
According to the Brazilian educational laws, the inclusion of students targeted by Special Education shall be in regular schools, offering them the Special Educational Services in resources room, during the shift opposite to the class hours. However, to receive such services, the students need to be identified as special education targets, that is, disabled students, those with Global Development Disorders, and those with High Abilities/Giftedness. Due to the lack of information in the field of High Abilities/Giftedness, these students continue to be neglected in their special educational needs. This research aimed at investigate the learning process of a child showing High Abilities/Giftedness associated to Asperger s Disorder, considering the executive function and the Mind Theory, thus contributing to qualify the Educational Special Services. As to the methodology, the research had a qualitative approach, adopting the case study as methodological procedure. The participants were a public elementary school student with Asperger s Distorder and High Abilities/Giftedness,his parents, teachers and Special Education teacher. Data were gathered using daily records and a semistructured interview, and were studied according to content analysis. The research allowed assessing that the educational proposals and evaluations previously made on this case basically focused behavioral issues where deficits appeared, instead of also encouraging and developing potentials in those areas where the student showed interests and presented good achievement. In order to change this reality and improve the educational services, good investments on teachers education and training would be necessary so as they could become authors of significant changes when joining the new knowledge to their professional practices.